Why nation-building matters : political consolidation, building security forces, and economic development in failed and fragile states - Mines, Keith W. (Diplomats and diplomacy series, 2020)
"Why Nation-Building Matters establishes a framework for building security forces, economic development, and political consolidation that blends soft and hard power into a deployable and effective package"--